2017
DOI: 10.1016/j.jphys.2017.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Home-based telerehabilitation is not inferior to a centre-based program in patients with chronic heart failure: a randomised trial

Abstract: ACTRN12613000390785. [Hwang R, Bruning J, Morris NR, Mandrusiak A, Russell T (2017) Home-based telerehabilitation is not inferior to a centre-based program in patients with chronic heart failure: a randomised trial. Journal of Physiotherapy 63: 101-107].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
411
2
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(436 citation statements)
references
References 28 publications
9
411
2
14
Order By: Relevance
“…30 Hwang et al enrolled 53 participants with HF into either home-based or conventional CR and found no significant difference with respect to the 6-minute-walk performance test. 31 Similarly, Moholdt and colleagues evaluated differences in oxygen (O2) uptake and HRQoL between facility-based and home-based CR and found no difference between groups in either O2 uptake and HRQoL. 32 A meta-analysis of 17 RCTs that included 2172 patients found no significant differences in mortality, major acute CVD events, exercise capacity, and most other markers of CV health when comparing home-based versus center-based CR.…”
Section: Modes Of Delivering Etmentioning
confidence: 99%
“…30 Hwang et al enrolled 53 participants with HF into either home-based or conventional CR and found no significant difference with respect to the 6-minute-walk performance test. 31 Similarly, Moholdt and colleagues evaluated differences in oxygen (O2) uptake and HRQoL between facility-based and home-based CR and found no difference between groups in either O2 uptake and HRQoL. 32 A meta-analysis of 17 RCTs that included 2172 patients found no significant differences in mortality, major acute CVD events, exercise capacity, and most other markers of CV health when comparing home-based versus center-based CR.…”
Section: Modes Of Delivering Etmentioning
confidence: 99%
“…This telerehabilitation program within the randomised controlled trial consisted of a 12-week group-based exercise and education intervention delivered into the patient's home twice weekly using an online videoconferencing platform (Hwang et al, 2017a). Results verified the primary research hypothesis that the change in distance on the 6 minute walk test (6MWD) from baseline to the end of the rehabilitation program in the telerehabilitation group was not inferior to the control group.…”
Section: Telerehabilitation Interventionmentioning
confidence: 57%
“…Emma Thomas 1 , Robyn Gallagher 2 and Sherry L Grace 3,4 To the Editor The paper by Yeo et al 1 makes the case for continuing cardiac rehabilitation (CR) during COVID-19, asserting that there is 'no better time than now for CR providers to explore and implement methods to improve or supplement existing programs'. In a time where conventionally-delivered programmes are being forced to close, some are considering the opportunity to transition towards (or expand) digital health formats.…”
Section: Future-proofing Cardiac Rehabilitation: Transitioning Servicmentioning
confidence: 99%
“…However, it must be mentioned that there is much more to learn about what makes mHealth applications appealing and how these interventions can be used for long-term cardiovascular disease management. 3 Videoconferencing offers the additional advantage of enabling providers to see and hear their patients (and vice versa); it can enable you to develop a therapeutic rapport, get a sense of a patient's health and well-being, supervise exercise remotely (either through videoconferencing software demonstrated by Hwang et al 4 or via a bespoke telerehabilitation platform and remote monitoring devices demonstrated by Maddison et al 5 ) and provide feedback and support, as well as share screens and files for educational and counselling purposes and to illustrate required actions. Videoconferencing also allows for groups, 3 therefore enhancing efficiency and providing the opportunity for participants to share experiences.…”
Section: Future-proofing Cardiac Rehabilitation: Transitioning Servicmentioning
confidence: 99%